2014
DOI: 10.1142/s0219091514500167
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Bankruptcy, Soft Budget Constraints, and Business Group Affiliation: Evidence from Indian Firms

Abstract: We examine the ex-ante performance of 1185 firms that filed for bankruptcy between 1992 and 2009. Evidence suggests that firm specific poor operating performance and industry wide distress are the principal causes (contributing 42% each for cash flow shortfall) of corporate distress. We observe vitiating investment, operating, and financing performance of the sample firms starting from four years prior to their bankruptcy. Further, we report less severe decline in capital expenditure in the case of state contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Business group affiliation. Business group affiliation is a significant feature of Indian companies, which influences the capital structure and financial performance (Gopalan et al, 2007;Bhaumik et al, 2012;Komera and Lukose, 2014) (Table I).…”
Section: Determinants Of Capital Structurementioning
confidence: 99%
“…Business group affiliation. Business group affiliation is a significant feature of Indian companies, which influences the capital structure and financial performance (Gopalan et al, 2007;Bhaumik et al, 2012;Komera and Lukose, 2014) (Table I).…”
Section: Determinants Of Capital Structurementioning
confidence: 99%
“…Research from various angles confirms that Indian business group firms share capital (Lensink, Van der Molen, & Gangopadhyay, 2003)) and risk (Komera & Lukose PJ, 2014). Efficient capital and risk sharing would reduce group firms' costs of capital; but Indian groups' capital and risk sharing is not necessarily efficient (Chacar & Vissa, 2005).…”
Section: Business Groups and India's New Middle-income Economymentioning
confidence: 99%
“…Politically connected firms benefit from the governments, from reduced regulations to support when facing financial distress (Faccio et al, 2002). Furthermore, Komera & Jijo Lukose (2014) found that business group affiliations exhibit a weak effect of soft budget constraints. Therefore, group affiliates do not need to increase cash reserves when facing cash flow uncertainty due to the internal capital market existence (Locorotondo, Dewaelheyns, and Van Hulle 2014).…”
Section: Business Group Affiliation and Cash Reservesmentioning
confidence: 99%
“…The model refers to several prior studies (R. R. Chen et al, 2018;Komera & Jijo Lukose, 2014). Furthermore, we also individually investigate the relationship between state ownership and GPR on cash reserves, with the following regression model in equation 3.…”
Section: Empirical Modelmentioning
confidence: 99%
See 1 more Smart Citation